EDUKASI MENGENAI PENTINGNYA DATA SCIENCE UNTUK MASA DEPAN - Ibnu Mansyur Hamdani; Syamsuri Syamsuri; Hasria Alang; Nurul Fuady Adhalia H (Jurnal Abdimas Bina Bangsa, 2023)
Artificial Intelligence (AI) is one of the developing technologies. AI has several capabilities that make it important to apply that is being able to solve complex problems, perform high-level computational processes, increase accuracy, and make decisions. One of the domains of AI is Data Science, which can forecast, predict, and recommend. Based on the capabilities of AI, especially Data Science, it is necessary to conduct education about AI and its applications. Education provided by online through a video conferencing application. The stages of implementing activities consist of planning, implementation, and evaluation. The results of the implementation of the activities were satisfying as shown by the results of the post test and the enthusiasm of the participants